(untitled) (IAHS Medical Journal, 2024)
Background: More than 75% of the population live in rural area in Bangladesh and morbidity and mortality due to Non-Communicable Diseases (NCDs) has increased over the last few decades in this country. Hypertension is a significant risk factor for NCDs, specifically cardiovascular disease. This study aimed to determine hypertension prevalence and associated factors among Bangladeshi adults in rural areas. Materials and methods: This cross-sectional study was conducted in selected rural areas in the Chattogram district of Bangladesh from January 2014 to December 2014. A total of 2500 individuals aged 18 years and above were determined by a multistage sampling method. Self-reported sociodemographic and hypertension-related data were collected using a structured case record form, and blood pressure was measured. Results: The overall prevalence of hypertension was 32.5% (812/2500) [95% confidence interval (CI), 30.7-34.3] (Men: 34.4%, Women: 30.9%). The prevalence of hypertension was 21.1% and 43.6% in the £40 and >40 years age group, respectively (p<0.001). Hypertension had no association with the gender, educational level and monthly income of the respondents. Overall, 1268 (50.7%, 95% CI 48.8-52.7%) of the study participants had ever had their blood pressure measured. Among the 812 people with hypertension, 478 (58.9%, CI 55.5-62.2%) were aware of the disease. Of those familiar with the disease, 404 (84.5% CI 81.0-87.5%) were on treatment, and 285 (70.5%, CI 64.2-74.9%) had achieved disease control. Only 315 (38.8%, CI 35.542.2) were controlled among all people with hypertension. Conclusion: Hypertension is highly prevalent (One in three) in Bangladeshi rural adults, while awareness, treatment, and control are low. The integrated context specific program must be designed and implemented at scale through a primary healthcare approach. IAHS Medical Journal Volume 6(2) December 2023; 78-82